Proximate and calcium analysis of nixtamalized corn grits as a raw material of Gorontalo traditional meal, Indonesia - SUNARTO KADIR; LISNA AHMAD; YOYANDA BAIT (Smujo International, 2019)
Abstract. Kadir S, Ahmad L, Bait Y. 2019. Proximate and calcium analysis of nixtamalized corn grits as a raw material of Gorontalo traditional meal, Indonesia. Nusantara Bioscience 11: 56-62. This study aims to find out the influence of additional lime concentration and the length of boiling time toward the proximate and calcium grits of corn (Zea mays L). The study was conducted using a randomized group factorial design of two factors. The first factor is calcium concentration consisted of three treatments; 0.5%, 1%, and 1.5%, and the second factor is the length of boiling time, consisting of two treatments; the 60-minute boiling time, and the 30-minute boiling time. The parameters of this study were water content, ash content, fat content, protein content, carbohydrate content, and calcium content. The ANOVA analysis reveals that the treatment of calcium concentration, and the length of boiling time insignificantly influence the water content, ash, protein, fat, carbohydrate, and calcium contents of nixtamal corn grits. Grits of nixtamal corn produced in this study has water content of 10.54-11.33%, ash content of 1.34-1.39%, protein content of 9.11-9.40%, fat content of 3.36-3.59%, carbohydrate content of 74.44-75.36%, and calcium content of 10.15-10.92%.